2020
DOI: 10.1111/pce.13896
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux from the chloroplast provides signals controlling photosynthetic acclimation to cold in Arabidopsis thaliana

Abstract: Photosynthesis is especially sensitive to environmental conditions, and the composition of the photosynthetic apparatus can be modulated in response to environmental change, a process termed photosynthetic acclimation. Previously, we identified a role for a cytosolic fumarase, FUM2 in acclimation to low temperature in Arabidopsis thaliana. Mutant lines lacking FUM2 were unable to acclimate their photosynthetic apparatus to cold. Here, using gas exchange measurements and metabolite assays of acclimating and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In terms of temperature, photosynthesis shows different responses when plants are exposed to heat or cold, although some of their signalling pathways are shared (reviewed by Sharma et al 2020; Choudjury et al 2013). Previously, we observed that photosynthetic acclimation to cold is dependent on the presence of FUM2 activity or protein (Dyson et al, 2016; Herrmann et al 2020). Thus, with the aim of understanding further the role of FUM2 and fumarate in the photosynthetic acclimation response to temperature, we analysed how its accumulation changes across the physiological temperature range in different genotypes of Arabidopsis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of temperature, photosynthesis shows different responses when plants are exposed to heat or cold, although some of their signalling pathways are shared (reviewed by Sharma et al 2020; Choudjury et al 2013). Previously, we observed that photosynthetic acclimation to cold is dependent on the presence of FUM2 activity or protein (Dyson et al, 2016; Herrmann et al 2020). Thus, with the aim of understanding further the role of FUM2 and fumarate in the photosynthetic acclimation response to temperature, we analysed how its accumulation changes across the physiological temperature range in different genotypes of Arabidopsis.…”
Section: Resultsmentioning
confidence: 99%
“…Malate and fumarate represent important diurnal carbon stores in Arabidopsis, and their accumulation tends to increase at low temperature (Dyson et al 2016; Herrmann et al 2019b; Herrmann et al 2020). The Arabidopsis ecotype C24 has previously been reported to have a reduced capacity for cytosolic fumarate synthesis, while the knockout mutant fum2 is impaired in fumarate accumulation (Riewe et al, 2016; Pracharoenwattana et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As chloroplasts are very sensitive to environmental fluctuations, dynamic proteome changes may represent a key factor for understanding their responses to abiotic stresses [11]. The most recent chloroplast proteomics studieshave aimed to identify (1) changes induced by biotic and abiotic stresses [12][13][14][15][16], (2) mechanisms of remodeling and reprogramming of plant metabolism [17,18], (3) biogenesis and senescence [19][20][21], (4) chloroplast development [22,23],in addition to (5) novel techniques for increasing proteome coverage [24][25][26].…”
Section: Introductionmentioning
confidence: 99%